Sulfotransferase SULT1A1 activity in hair follicle, a prognostic marker of response to the minoxidil treatment in patients with androgenetic alopecia: a review - Pietrauszka, Kornelia; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Androgenetic alopecia (AGA) is a very common type of alopecia in men and women. It may have a negative effect on the quality of life. The most widely used pharmaceutical treatment for AGA is topical minoxidil and it is also the only external treatment of pattern hair loss. There are two forms of this treatment – 5% and 2% minoxidil. The correlation between SULT1A1 expression in the scalp and minoxidil response has been previously reported. Due to the prolonged treatment time required to elicit a therapeutic response (approximately 6 months) combined with the variable efficacy of minoxidil in the general population, expression of SULT1A1 as a biomarker for predicting treatment response would have a significant clinical utility.